Find the function rule

(-2,9) (-1,4) (0,-1) (1,-6) (2,-11)

I think the function rule is you subtract 5 from the y as you go on.

1 answer

y = - ( 5 x + 1 )

x = - 2

y = - [ 5 * ( - 2 ) + 1 ] = - ( - 10 + 1 ) = - ( - 9 ) = 9

x = - 1

y = - [ 5 * ( - 1 ) + 1 ] = - ( - 5 + 1 ) = - ( - 4 ) = 4

x = 0

y = - ( 5 * 0 + 1 ) = - ( 0 + 1 ) = - 1

x = 1

y = - ( 5 * 1 + 1 ) = - ( 5 + 1 ) = - 6

x = 2

y = - ( 5 * 2 + 1 ) = - ( 10 + 1 ) = - 11

Of course you can write:

- ( 5 x + 1 ) = - 5 x -1
Similar Questions
  1. 3. What is the rule for the function shown in the table? (1 point)x = -1, 0, 1, 2 y = -2, 1, 4, 7 A.y = 1/3x + 1 B.y = 3x + 1
    1. answers icon 35 answers
  2. Write a rule for the function represented by the table.x y 0 13 1 28 2 43 3 58 y= 15 + 13x y= 14 + 12x y= 13 + 15x** y= 12 + 14x
    1. answers icon 2 answers
  3. Write a function rule for the data in the table.Input (x) 1 2 3 4 5 Output(y) 6 8 10 12 14 I've been looking at this for about
    1. answers icon 8 answers
    1. answers icon 2 answers
more similar questions